BIBLIOMETRIC ANALYSIS OF JOURNAL ARTICLES PUBLISHED BY SOUTHEAST ASIAN CHEMICAL ENGINEERING RESEARCHERS - Chun, Yang Yin (Malaysian Journal of Library and Information Science, 2009)
In this study, journal articles publication trends among Southeast Asian chemical engineering (CE) researchers from 1996 to 2008 are analyzed through bibliometric means. The focus of the study is on the journal publication trend of CE researchers rather than the publication trend of papers that fall within the area of CE. Bibliometric data are obtained from Scopus, Journal Citation Reports® as well as the SCImago Journal & Country Rank online academic databases. The study shows that Singapore tops the amount of journal articles published by CE researchers from 1996 to 2008, followed by Malaysia, Thailand, Indonesia and Philippines. Overall observation indicates that journal articles publication trends among Southeast Asian CE researchers are highly dissimilar and noteworthy. Results accrued from this study are useful indicators for journal publishers to determine the publishing behaviour of CE researchers as well as for each country’s science policy makers to formulate appropriate research policies and directions.